Building a Cisco wireless LAN - Ouellet, Eric.; Padjen, Robert; Pfund, Arthur (Rockland, Mass. : Syngress Media ; London : International Thomson, 2002)
Enable enterprise-wide information access using Cisco wireless networks Wireless networks are rapidly becoming a viable alternative to traditional wired LANs (Local Area Networks), mainly because of the convenience they provide. By implementing a wireless network, companies eliminate the need and expense of installing fixed cables, outlet ports or patch panels. Building a Cisco Wireless LAN is for individuals designing and supporting a Cisco wireless LAN. The book contains detailed information on the process for the thorough and accurate network design for the Cisco 340, 350, and UBR 7200 series. The contains detailed information on the configuration and troubleshooting of a Cisco WLAN installation. The book offers an introduction to wireless technology from the fundamental principles to the actual implementation. The first book for Cisco LAN users looking to upgrade to a wireless network Ideal for Network administrators looking into wireless network technology for the first time.
Includes index.
Keywords: Local area networks (Computer networks); Electronic books